Capillary flow control in nanochannels via hybrid surface. Issue 4 (4th January 2016) - Ye, Ziran; Li, Shunbo; Wang, Cong; Shen, Rong; Wen, Weijia
Abstract : We report a simple and effective approach to control the speed of capillary flow in nanochannels in a quantitative manner. Abstract : We report a simple and effective approach to control the speed of capillary flow in nanochannels in a quantitative manner. Hydrophobic surface patterns were fabricated on both top and bottom walls of hydrophilic nanochannels to reduce the speed of fluid. Capillary flow speed can be precisely controlled in the nanochannel by modifying the hydrophobicity ratio due to the flow characteristics on hydrophobic/hydrophilic surfaces. Without any additional energy source and equipment, this phenomenon can be realized solely by the wetting property of the patterned surface. We attribute this achievement to the significant surface effect on the liquid behavior due to the extremely large surface-to-volume ratio in the nanochannel. This flow control method is helpful to obtain a detailed and thorough understanding of the dynamic filling behavior of capillary flow at the nanoscale, as well as applicable to a wide variety of nanofluidics-based analysis systems.